Preliminary study on the initiation mechanism of hydrodynamic-driven bedding rock landslides based on physical model tests - Yating Tang; Jie Tan; Changdong Li; Bingchen Li; Wenjuan Zhou (地质科技通报, 2022)
Hydrodynamic-driven bedding rock landslides are the focus of research in the field of landslide geological hazards due to their large number, frequent disasters, and excessive harm. However, the understanding of the initiation mechanism of landslides is still insufficient, and the accurate prediction of landslides still faces great challenges. Because of this, this paper takes moderate-dip angle bedding rock landslides with weak interlayers as the research object and conducts a series of landslide model tests under the action of hydrodynamics by constructing an ideal single-layer landslide physical model. On this basis, the macroscopic deformation evolution process of the landslide and the erosion degradation characteristics of the slide zone soil is analyzed in depth. The results show that the failure of bedding rock landslides is associated with the slip surface roughness and dip angle and can go through four stages: the initial deformation stage, uniform deformation stage, accelerated deformation stage, and failure stage.The seepage erosion in the sliding zone causes the loss of aggregates, which reduces the shear strength and causes the slope to slide. Simultaneously, the compression-shear action and the deformation of the overlying slope also adversely affect erosion strength.Based on the variation law of soil cohesion in the sliding zone with hydraulic gradient and erosion time, a seepage-driven evolution model of soil cohesion in the sliding zone is proposed, which can describe the degradation process of soil cohesion in the sliding zone well. The existence of sliding surface roughness not only significantly affects the deterioration law of the sliding zone, but also changes the failure modes of different regions of the sliding zone. By considering the influence of the roughness on the failure modes of different areas of the sliding zone, the multi-effect correlation analysis of dynamic water is carried out, and the mechanical model of the landslide is established, which realizes the effective evaluation of the dynamic stability of the landslide. The research achievements in this study can provide a theoretical reference for predicting and preventing actual hydrodynamic-driven bedding rock landslides.